Agents for preventing the adhesion of harmful air substances

JP7637468B2Active Publication Date: 2025-02-28KAO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2019106323
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-06-06
Publication Date
2025-02-28
Estimated Expiration
2039-06-06

AI Technical Summary

Benefits of technology

【0006】 本発明によれば、大気有害物質に対する高い付着抑制効果を有し、かつ塗布後の感触の低下を抑制できる大気有害物質付着抑制剤、及び該大気有害物質付着抑制剤を用いる大気有害物質の付着抑制方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637468000002
    Figure 0007637468000002
  • Figure 0007637468000001
    Figure 0007637468000001
Patent Text Reader

Abstract

To provide an air hazardous substance adhesion inhibiting agent that has a high adhesion inhibiting effect on air hazardous substances and can suppress the deterioration of the feel after application, and a method of inhibiting the adhesion of air hazardous substances using the air hazardous substance adhesion inhibiting agent.SOLUTION: [1] Provided is an air hazardous substance adhesion inhibiting agent containing inorganic particles (A), the average particle diameter DA of the inorganic particles (A) being 1 μm or more and 50 μm or less, and the surface roughness Ra of the inorganic particles (A) being 10 nm or more and 50nm or less. [2] Also provided is a method of inhibiting the adhesion of air hazardous substances, in which method the air hazardous substance adhesion inhibiting agent described in the above item [1] is applied to a surface of a solid, to thereby inhibiting the air hazardous substances from adhering to the surface of the solid.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an agent for inhibiting the adhesion of atmospheric hazardous substances, and a method for inhibiting the adhesion of atmospheric hazardous substances using the agent for inhibiting the adhesion of atmospheric hazardous substances. [Background technology]

[0002] Since inorganic particles exhibit many functions, their application in a wide range of industrial fields has been studied. For example, a technology is known that uses the optical properties of inorganic particles to make unevenness on the skin less noticeable. Patent Document 1 describes a cosmetic composition that contains a surface-coated powder obtained by coating the surface of at least one type of powder particles selected from metal oxides, metal hydroxides, and / or complexes containing them with a specific copolymer, spherical particles with an average primary particle size of 25 to 35 μm, and an oil agent, for the purpose of providing a cosmetic composition having hiding properties, etc. In addition, a technique utilizing the adsorption ability of the pores of an inorganic porous body is also known. For example, Patent Document 2 describes a skin care cosmetic that contains a specific amount of magnesium aluminometasilicate and a specific amount of an ultraviolet protection agent as a skin care cosmetic that protects the skin from external stimuli such as air pollutants. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-250917 A [Patent Document 2] International Publication No. 2014 / 136993 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, airborne harmful substances such as pollen from cedars and cypresses, soot, dust, and yellow sand have become a problem because they cause various health damage to humans. Among the harmful substances, particulate matter with a diameter of 2.5 μm or less, called PM2.5, is composed of carbon components, sulfates, nitrates, ammonium salts, and other components, and it is known that PM2.5 and yellow sand can cause circulatory and respiratory diseases when inhaled. It has also been pointed out that PM2.5, pollen, and yellow sand can cause skin problems by adhering to or penetrating the skin. For example, Shiraiwa et al. have reported on the damage caused to the skin by PM2.5 (Nature Chemistry 3, 291-295 (2011)). Therefore, in order to reduce the health damage caused by exposure to harmful substances in the air, there is a high demand for adhesion inhibitors that suppress the adhesion of harmful substances to various solid surfaces around us, such as skin, hair, and clothing. However, the technology of Patent Document 1 is aimed at concealing unevenness of the skin, and the adhesion suppression effect is insufficient. In addition, the technology of Patent Document 2 uses the adsorption ability of magnesium aluminometasilicate to adsorb harmful substances in the air and suppress adhesion to the skin, so the adhesion suppression effect is insufficient. In addition, inorganic particles in powder form have a strong squeaky feeling, and may have a poor feel especially after application to the skin. Therefore, it is also required to suppress the deterioration of the feel after application of the adhesion suppressant to a solid surface. The present invention aims to provide an air hazardous substance adhesion inhibitor that has a high adhesion inhibitory effect against air hazardous substances and can inhibit a decrease in the feel after application, and a method for inhibiting the adhesion of air hazardous substances using the air hazardous substance adhesion inhibitor. [Means for solving the problem]

[0005] The inventors have discovered that the above problem can be solved by setting the surface roughness Ra of inorganic particles within a predetermined range to enhance the effect of inhibiting the adhesion of atmospheric harmful substances, while setting the average particle size of the inorganic particles within a predetermined range to inhibit deterioration in the feel after application. That is, the present invention provides the following [1] and [2]. [1] An agent for suppressing the adhesion of air hazardous substances containing inorganic particles (A), The average particle diameter D of the inorganic particles (A) A and the surface roughness Ra of the inorganic particles (A) is 10 nm or more and 50 nm or less. [2] A method for inhibiting adhesion of atmospheric hazardous substances, comprising applying the agent for inhibiting adhesion of atmospheric hazardous substances to a solid surface, the agent being described in [1] above. Effect of the Invention

[0006] According to the present invention, it is possible to provide an air hazardous substance adhesion inhibitor that has a high adhesion inhibitory effect against air hazardous substances and can suppress a decrease in the feel after application, and a method for inhibiting the adhesion of air hazardous substances using the air hazardous substance adhesion inhibitor. [Brief description of the drawings]

[0007] [Figure 1] FIG. 4 is a schematic side view showing a method for evaluating the adhesion suppression effect. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] [Air hazardous substance adhesion inhibitor] The agent for suppressing the adhesion of atmospheric hazardous substances (hereinafter also referred to as "adhesion suppressor") of the present invention is an agent for suppressing the adhesion of atmospheric hazardous substances containing inorganic particles (A), and the inorganic particles (A) have an average particle diameter D A is 1 μm or more and 50 μm or less, and the surface roughness Ra of the inorganic particles (A) is 10 nm or more and 50 nm or less. In the present invention, "harmful air substances" refers to air pollutants such as pollen from cedar, cypress, etc.; soot and smoke such as sulfur oxides, soot dust, nitrogen oxides, particulate matter, automobile exhaust gas, harmful air pollutants such as benzene, trichloroethylene, tetrachloroethylene, and particles containing volatile organic compounds (VOCs); and harmful substances suspended in the air such as yellow sand (including PM2.5).

[0009] The adhesion inhibitor of the present invention has a high adhesion inhibitory effect on atmospheric hazardous substances, particularly fine particulate atmospheric hazardous substances, and can suppress deterioration in the feel after application of the adhesion inhibitor. The reason for this is not clear, but is thought to be as follows. The inorganic particles contained in the adhesion inhibitor of the present invention have a surface roughness Ra within a predetermined range, so that when the adhesion inhibitor is applied to a solid surface, it forms localized nano-sized irregularities on the solid surface. When such a surface comes into contact with an air hazardous substance, the contact area becomes smaller, and it is believed that the adhesion of the hazardous substance can be effectively suppressed. Furthermore, since the average particle size of the inorganic particles is within a predetermined range, it is believed that the deterioration of the feel after application of the adhesion inhibitor can be suppressed.

[0010] <Inorganic particles (A)> From the viewpoint of improving the adhesion suppression effect, the surface roughness Ra of the inorganic particles (A) is 50 nm or less, preferably 40 nm or less, more preferably 35 nm or less, even more preferably 30 nm or less, and 10 nm or more, preferably 12 nm or more, more preferably 14 nm or more, even more preferably 15 nm or more. More specifically, from the viewpoint of improving the adhesion suppression effect, the surface roughness Ra is preferably 10 to 40 nm, more preferably 12 to 40 nm, even more preferably 12 to 35 nm, even more preferably 14 to 35 nm, even more preferably 15 to 35 nm, and even more preferably 15 to 30 nm. The surface roughness Ra is measured by the method described in the examples.

[0011] Average particle size D of inorganic particles (A) A From the viewpoint of suppressing deterioration of the feel after application, the average particle diameter D is 1 μm or more, preferably 1.5 μm or more, more preferably 2 μm or more, and is 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less, even more preferably 25 μm or less, still more preferably 20 μm or less, still more preferably 15 μm or less, and still more preferably 10 μm or less. More specifically, the average particle diameter D AFrom the viewpoint of suppressing deterioration in the feel after application, the thickness is preferably 1 to 40 μm, more preferably 1 to 30 μm, even more preferably 1 to 25 μm, still more preferably 1 to 20 μm, still more preferably 1 to 15 μm, still more preferably 1 to 10 μm, still more preferably 1.5 to 10 μm, and still more preferably 2 to 10 μm. The average particle diameter D A is measured by the method described in the Examples.

[0012] Specific examples of the inorganic particles (A) include silicon dioxide (silica), silicon nitride, silicon carbide, aluminum silicate, magnesium silicate, calcium silicate, and other silicon-containing compounds; titanium oxide, zinc oxide, aluminum oxide (alumina), magnesium oxide, calcium oxide, zirconium oxide, iron oxide, cerium oxide, chromium oxide, and other metal oxides; magnesium carbonate, calcium carbonate, barium sulfate, barium carbonate, magnesium bicarbonate, calcium bicarbonate, lithium carbonate, calcium phosphate, titanium phosphate, silver chloride, silver bromide, and other metal salts; magnesium hydroxide, aluminum hydroxide, calcium hydroxide, and other metal hydroxides; titanium, iron, chromium, nickel, gold, silver, platinum, copper, lead, zinc, and other metals and alloys thereof; diamond; boron nitride, boron carbide, and other boron-containing compounds; titanium carbide, tantalum carbide, zirconium carbide, and other metal carbides; aluminum nitride, titanium nitride, and other metal nitrides; and mixtures of magnesium aluminometasilicate (magnesium aluminosilicate). These inorganic particles can be used alone or in combination of two or more kinds.

[0013] Among these, from the viewpoints of improving the adhesion suppression effect and suppressing deterioration in the feel after application, the inorganic particles (A) are preferably particles containing one or more selected from a silicon-containing compound, a metal oxide, a metal salt, a metal nitride, and a metal carbide, more preferably particles containing one or more selected from a silicon-containing compound and a metal oxide, even more preferably particles containing one or more selected from silica, calcium silicate, titanium oxide, zinc oxide, and magnesium aluminometasilicate, and even more preferably particles containing one or more selected from silica and calcium silicate. The inorganic fine particles (A) may be either untreated or surface-treated. The content of the inorganic substance in the inorganic particles (A) is preferably 60% by mass or more, more preferably 70% by mass or more, and preferably 100% by mass or less. In addition, when the inorganic particles (A) are surface-treated, the mass, adhesion amount, and average particle diameter D A The surface roughness Ra is the mass including the surface treatment agent, the amount of adhesion, and the average particle diameter D A and surface roughness Ra.

[0014] The inorganic particles (A) may be either easily disintegrating particles or non-disintegrating particles. In the present invention, "disintegrability" refers to the ease with which inorganic particles disintegrate when rubbed with a predetermined load. Specifically, when rubbed back and forth 10 times using a surface property measuring device Tribogear Type: 14 (manufactured by Shinto Scientific Co., Ltd.) according to the method specified in the Examples, particles having a particle size ratio represented by the following formula (I) of less than 50% are defined as "disintegrable particles," and particles having a particle size ratio represented by the following formula (I) of 50% or more are defined as "non-disintegrable particles." Particle size ratio before and after scraping (%) = (average particle size after scraping D A ' / Average particle size before abrasion D A )×100 (I)

[0015] The inorganic particles (A) are preferably easily disintegrating particles from the viewpoint of improving the adhesion suppression effect, and are preferably non-disintegrating particles from the viewpoint of improving the feel after application. In the present invention, the adhesion inhibitor may use a combination of easily disintegrating particles and non-disintegrating particles as the inorganic particles (A) from the viewpoint of improving the adhesion inhibitory effect and improving the feel after application. When disintegrable particles and non-disintegrable particles are used in combination as the inorganic particles (A), the mass ratio of the disintegrable particles to the non-disintegrable particles in the adhesion inhibitor (disintegrable particles / non-disintegrable particles) is preferably 0.1 / 99.9 or more, more preferably 10 / 90 or more, and even more preferably 30 / 70 or more, from the viewpoint of improving the adhesion inhibition effect, and is preferably 99.9 / 0.1 or less, more preferably 90 / 10 or less, and even more preferably 70 / 30 or less, from the viewpoint of improving the feel after application.

[0016] When the inorganic particles (A) are easily disintegrable particles, from the viewpoint of improving the adhesion suppression effect and suppressing deterioration of the feel after application, the inorganic particles (A) are preferably secondary particles formed by agglomeration of primary particles, and the average secondary particle diameter thereof is the above-mentioned average particle diameter D A It is preferable that: When the inorganic particles (A) are secondary particles, the average primary particle diameter d of the inorganic particles (A) A From the viewpoint of improving the adhesion suppression effect, the average primary particle diameter d is preferably 1 nm or more, more preferably 3 nm or more, even more preferably 5 nm or more, and even more preferably 7 nm or more, and is preferably 50 nm or less, more preferably 40 nm or less, even more preferably 30 nm or less, even more preferably 25 nm or less, even more preferably 20 nm or less, and even more preferably 15 nm or less. A is measured by the method described in the Examples. More specifically, the average primary particle diameter d AFrom the viewpoint of improving the adhesion suppression effect, the thickness is preferably 1 to 50 nm, more preferably 3 to 50 nm, even more preferably 3 to 40 nm, still more preferably 3 to 30 nm, still more preferably 3 to 25 nm, still more preferably 5 to 25 nm, still more preferably 5 to 20 nm, still more preferably 5 to 15 nm, and still more preferably 7 to 15 nm. When the inorganic particles (A) are secondary particles, the surface roughness Ra is equal to or smaller than the average primary particle diameter d A Therefore, the average primary particle diameter d A By adjusting the above, the surface roughness Ra can be controlled.

[0017] The oil absorption of the inorganic particles (A) is preferably 50 mL / 100 g or more, more preferably 100 mL / 100 g or more, even more preferably 130 mL / 100 g or more, and is preferably 700 mL / 100 g or less, more preferably 600 mL / 100 g or less, even more preferably 500 mL / 100 g or less. The oil absorption can be measured in accordance with JIS K 5101-13-2:2004.

[0018] The inorganic particles (A) may be prepared by preparation or may be commercially available. When preparing the inorganic particles (A), a known method can be used depending on the type of inorganic substance constituting the particles (A). For example, when the inorganic particles (A) are particles containing silica (hereinafter also referred to as "silica particles"), they can be prepared by high-temperature methods such as flame hydrolysis and arc methods; and wet methods such as precipitation and gel methods. Among these, when the inorganic particles (A) are secondary particles, they are preferably prepared by a gel method from the viewpoint of adjusting the primary particle diameter and improving the adhesion suppression effect. The gel method can be carried out, for example, by emulsifying sodium silicate in a non-polar organic solvent containing a surfactant to obtain a W / O emulsion, followed by gelation. Average particle diameter D of silica particles A can be controlled by adjusting the W / O emulsion diameter. The gelation is preferably carried out in an acidic region, for example, by a neutralization reaction of a mineral acid such as sulfuric acid, which allows aggregation of the primary silica particles to occur while suppressing the growth of the primary silica particles, thereby forming secondary silica particles. Next, the aging process after gelation controls the pore structure such as the specific surface area, pore diameter, pore volume, etc., and adjusts the primary particle diameter and the agglomeration of the primary particles, thereby adjusting the surface roughness Ra and disintegrability. From the viewpoint of improving the adhesion suppression effect, the silica particles are preferably disintegrable particles. From the viewpoint of improving the feel after application, the silica particles are preferably non-disintegrable particles. Commercially available inorganic particles (A) include silica particles such as Sunsphere H series (product name, manufactured by AGC Si-Tech Co., Ltd.); calcium silicate particles such as Fluorite R (product name, manufactured by Tomita Pharmaceutical Co., Ltd.); and the like.

[0019] The specific surface area of ​​the silica particles is preferably 100 m from the viewpoint of improving the adhesion suppression effect and suppressing deterioration of the feel after application. 2 / g or more, more preferably 300m 2 / g or more, more preferably 500m 2 / g or more, and preferably 1,000m 2 / g or less, more preferably 900m 2 / g or less, more preferably 800m 2 The specific surface area is a BET specific surface area measured in accordance with JIS Z 8830:2013. From the viewpoints of improving the adhesion suppression effect and suppressing deterioration in the feel after application, the pore diameter of the silica particles is preferably 1 nm or more, more preferably 3 nm or more, even more preferably 5 nm or more, and is preferably 20 nm or less, more preferably 17 nm or less, even more preferably 15 nm or less. From the viewpoints of improving the adhesion suppression effect and suppressing a decrease in the feel after application, the pore volume of the silica particles is preferably 0.3 mL / g or more, more preferably 0.5 mL / g or more, even more preferably 0.7 mL / g or more, and is preferably 3 mL / g or less, more preferably 2.7 mL / g or less, even more preferably 2.3 mL / g or less. The pore diameter and the pore volume can be measured by a gas adsorption method. Silica in silica particles (SiO 2 ) content is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 99% by mass or more, and is preferably 100% by mass or less.

[0020] The content of inorganic particles (A) in the air hazardous substance adhesion inhibitor is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and preferably 100% by mass or less, from the viewpoint of improving the adhesion inhibition effect and inhibiting deterioration in the feel after application.

[0021] The adhesion inhibitor of the present invention can be used as is without diluting it in a solvent or the like, but it can also be used by appropriately blending it with solvents, oils, and additives that are commonly used in cosmetics, etc., depending on the form or purpose of use. There is no particular limitation on the form of use of the adhesion inhibitor of the present invention. Examples of the form of use include any form such as mist, liquid, foam, paste, cream, etc., but it is preferably in the form of a liquid, paste, or cream, and more preferably in the form of a liquid.

[0022] The adhesion inhibitor of the present invention can be produced by a conventional method depending on the form of use, and can be produced by mixing the inorganic particles (A) and, if necessary, various additives by a known method. Additives can be blended in the range that does not inhibit the effects of the present invention. Examples of the additives include dyes, organic pigments, inorganic pigments, UV scattering agents, UV absorbers, fragrances, cosmetic ingredients, medicinal ingredients, pH adjusters, viscosity adjusters, moisturizers, oxidation inhibitors, bactericides, preservatives, and texture improvers such as polymer particles, other than inorganic particles (A). These can be used alone or in combination of two or more.

[0023] [Methods for preventing the adhesion of harmful substances to the atmosphere] The adhesion inhibitor of the present invention has a high adhesion inhibitory effect against atmospheric hazardous substances and can suppress deterioration in the feel after application, and is therefore preferably used as an adhesion inhibitor for atmospheric hazardous substances whose target for adhesion inhibition is a solid surface. That is, the adhesion inhibitor is preferably applied to a solid surface to inhibit adhesion of air hazardous substances to the solid surface. In the present invention, the term "solid surface" refers to the interface between a solid and the atmosphere. The solid may be either a biological solid or a non-biological solid. Biosolids include human and animal skin, hair, nails, and the like. Non-biological solids include glass, pottery, porcelain, enamel, tiles, ceramics, wood, and metal; synthetic resins such as polyethylene, polypropylene, melamine resin, polyamide resin, ABS resin, and FRP; natural fibers such as cotton, silk, and wool; and synthetic fibers such as polyester, nylon, and rayon. The shape of the solid surface is not particularly limited.

[0024] The method of applying the adhesion inhibitor to a solid surface can be appropriately selected depending on the shape of the solid surface. When the adhesion inhibitor is in the form of a liquid, foam, paste, or cream, it can usually be applied by coating or spraying as it is. The amount of the adhesion inhibitor applied to the solid surface is preferably 0.01 mg / cm as the adhesion amount of the inorganic particles (A) from the viewpoint of improving the adhesion suppression effect. 2 More preferably, 0.05 mg / cm 2 More preferably, 0.07 mg / cm2 and from the standpoint of appearance and feel, preferably 3 mg / cm 2 Less than 1 mg / cm, more preferably 1 mg / cm 2 More preferably, 0.5 mg / cm 2 More specifically, the amount of the adhesion inhibitor applied to the solid surface is preferably 0.01 to 3 mg / cm as the adhesion amount of the inorganic particles (A) from the viewpoint of improving the adhesion inhibitor effect and from the viewpoint of appearance and feel. 2 , more preferably 0.05 to 1 mg / cm 2 , and more preferably 0.07 to 0.5 mg / cm 2 It is.

[0025] From the viewpoint of the adhesion inhibitory effect and from the viewpoint of suppressing the deterioration of the feel after application, the adhesion inhibitor of the present invention is preferably applied to the skin surface as the solid surface to be inhibited from adhesion. That is, from the same viewpoint as above, the adhesion inhibitor is preferably applied to the skin surface and used in a method for inhibiting adhesion of atmospheric harmful substances to the skin. When applied to the skin, it can also be used as a material for imparting an effect of inhibiting adhesion of atmospheric harmful substances to skin external preparations, skin cosmetics, etc. Here, "applying to the skin surface" includes not only directly applying the adhesion inhibitor to the skin surface by hand, etc., but also adhering the adhesion inhibitor to the skin surface by spraying, etc. The amount of the adhesion inhibitor applied to the skin surface is preferably 0.01 mg / cm as the adhesion amount of inorganic particles (A) from the viewpoint of improving the adhesion inhibitory effect. 2 More preferably, 0.05 mg / cm 2 More preferably, 0.07 mg / cm 2 and from the standpoint of appearance and feel, preferably 3 mg / cm 2 Less than 1 mg / cm, more preferably 1 mg / cm 2 More preferably, 0.5 mg / cm 2 More specifically, the amount of the adhesion inhibitor applied to the skin surface is preferably 0.01 to 3 mg / cm as the adhesion amount of inorganic particles (A) from the viewpoint of improving the adhesion inhibitory effect and from the viewpoint of appearance and feel. 2, more preferably 0.05 to 1 mg / cm 2 , and more preferably 0.07 to 0.5 mg / cm 2 It is.

[0026] In addition to the above-mentioned embodiment, the present invention further discloses the following embodiments. <1> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) A and the surface roughness Ra of the inorganic particles (A) is 10 nm or more and 50 nm or less.

[0027] <2> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) A an average particle diameter of the inorganic particles (A) being 1 μm or more and 25 μm or less, a surface roughness Ra of the inorganic particles (A) being 10 nm or more and 50 nm or less, the inorganic particles (A) being particles containing one or more types selected from a silicon-containing compound, a metal oxide, a metal salt, a metal nitride, and a metal carbide, and the content of the inorganic particles (A) in the agent for inhibiting the adhesion of atmospheric harmful substances being 70 mass % or more and 100 mass % or less. <3> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) A an inorganic particle (A) having a diameter of 1 μm or more and a surface roughness Ra of 12 nm or more and 35 nm or less, the inorganic particle (A) being a particle containing one or more particles selected from silica, calcium silicate, titanium oxide, zinc oxide, and magnesium aluminometasilicate, and the content of the inorganic particle (A) in the agent for inhibiting the adhesion of atmospheric harmful substances is 80 mass % or more and 100 mass % or less. <4> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) Aan average particle diameter of the inorganic particles (A) being 1 μm or more and 10 μm or less, a surface roughness Ra of the inorganic particles (A) being 15 nm or more and 30 nm or less, the inorganic particles (A) being particles containing silica (silica particles), and a content of the inorganic particles (A) in the agent for inhibiting the adhesion of atmospheric harmful substances being 90 mass % or more and 100 mass % or less.

[0028] <5> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) A an average particle diameter of the inorganic particles (A) being 1 μm or more and 25 μm or less, a surface roughness Ra of the inorganic particles (A) being 10 nm or more and 50 nm or less, and the inorganic particles (A) being particles containing silica (silica particles). <6> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) A an average particle diameter of the inorganic particles (A) being 1 μm or more and 25 μm or less, a surface roughness Ra of the inorganic particles (A) being 10 nm or more and 40 nm or less, and the inorganic particles (A) being particles containing silica (silica particles). <7> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) A an average particle diameter of the inorganic particles (A) being 1 μm or more and 25 μm or less, a surface roughness Ra of the inorganic particles (A) being 15 nm or more and 35 nm or less, and the inorganic particles (A) being particles containing silica (silica particles). <8> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) A an average particle diameter of the inorganic particles (A) being 1 μm or more and 15 μm or less, a surface roughness Ra of the inorganic particles (A) being 10 nm or more and 50 nm or less, and the inorganic particles (A) being particles containing silica (silica particles). <9> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) Aan average particle diameter of the inorganic particles (A) being 1 μm or more and 10 μm or less, a surface roughness Ra of the inorganic particles (A) being 10 nm or more and 50 nm or less, and the inorganic particles (A) containing silica (silica particles). <10> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) A an average particle diameter of the inorganic particles (A) being 1 μm or more and 10 μm or less, a surface roughness Ra of the inorganic particles (A) being 15 nm or more and 35 nm or less, and the inorganic particles (A) being particles containing silica (silica particles).

[0029] <11> The inorganic particles (A) are non-disintegrating particles. <1> ~ <10> 2. The agent for suppressing adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <12> The inorganic particles (A) are easily disintegrable particles. <1> ~ <10> 2. The agent for suppressing adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <13> The inorganic particles (A) are secondary particles formed by agglomeration of primary particles, and have an average primary particle diameter d A is 3 nm or more and 50 nm or less, <12> 2. An agent for suppressing adhesion of harmful air substances as described above. <14> The inorganic particles (A) are secondary particles formed by agglomeration of primary particles, and have an average primary particle diameter d A is 3 nm or more and 25 nm or less, <12> 2. An agent for suppressing adhesion of harmful air substances as described above. <15> An agent for suppressing the adhesion of air hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) A is 1 μm or more and 10 μm or less, the surface roughness Ra of the inorganic particles (A) is 15 nm or more and 35 nm or less, the inorganic particles (A) are particles containing silica (silica particles), and the inorganic particles (A) have an average primary particle diameter d A An agent that inhibits the adhesion of harmful air substances, which are secondary particles formed by agglomeration of primary particles that are 3 nm or larger and 25 nm or smaller.

[0030] <16> The target of adhesion inhibition is a solid surface. <1> ~ <15> 2. The agent for suppressing adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <17> The target of adhesion inhibition is the skin surface. <1> ~ <15> 2. The agent for suppressing adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <18> The above <1> ~ <15> The agent for suppressing the adhesion of atmospheric hazardous substances according to any one of the above items is added to the composition in an amount of 0.01 mg / cm in terms of the amount of adhesion of inorganic particles (A). 2 More than 3mg / cm 2 A method for inhibiting adhesion of atmospheric hazardous substances, comprising applying the following to a solid surface to inhibit adhesion of the atmospheric hazardous substances to the solid surface. <19> The above <1> ~ <15> The agent for suppressing the adhesion of atmospheric hazardous substances according to any one of the above items is added to the composition in an amount of 0.01 mg / cm in terms of the amount of adhesion of inorganic particles (A). 2 More than 3mg / cm 2 A method for inhibiting adhesion of atmospheric hazardous substances to the skin surface by applying the following to the skin surface to inhibit adhesion of atmospheric hazardous substances to the skin surface. <20> The amount of inorganic particles (A) attached is 0.05 mg / cm 2 More than 1mg / cm 2 The above-mentioned <18> or <19> 2. A method for suppressing adhesion of harmful air substances according to claim 1. EXAMPLES

[0031] In the following examples and comparative examples, "%" means "% by mass" unless otherwise specified. Various physical properties were measured by the following methods.

[0032] (1) Average particle diameter D A Measurement Measurements were performed using a laser diffraction / scattering type particle size distribution analyzer (product name "LA-920", manufactured by Horiba, Ltd.) with ion-exchanged water as the dispersion medium. The relative refractive index was set to 1.10 for organic particles and 1.09 for inorganic particles. Measurements were performed using a flow cell under the following measurement conditions: circulation speed: 15, ultrasonic irradiation: none, distribution form: standard, particle size standard: volume.

[0033] (2) Average primary particle diameter d A Measurement When the measurement sample has a shape other than a plate shape, a dispersion of the measurement sample prepared in advance is placed on the sample stage of a transmission electron microscope (TEM) (trade name "JEM1400Plus", manufactured by JEOL Ltd.) and air-dried, and the maximum short diameters of 300 primary particles in an image observed with the TEM at a magnification of 50,000 times are measured, and the number average value is taken as the average primary particle diameter. Here, the maximum short diameter means the short diameter having the greatest length among the short diameters perpendicular to the long diameter. When the measurement sample had a plate-like shape, the thicknesses of 300 primary particles in an image observed under the same method and magnification conditions as above were measured, and the number average value was taken as the average primary particle diameter for each. The dispersion of the measurement sample was prepared by adding 95 g of ethanol as a solvent to 5 g of the measurement sample and subjecting the mixture to ultrasonic dispersion.

[0034] (3) Measurement of surface roughness Ra A dispersion of each particle (dispersion medium: ethanol, solid content concentration: 5%) was applied to artificial leather (product name "Laforet S2923", manufactured by Okamoto Shinwa Co., Ltd.) at a concentration of 2.0 mg / cm. 2 (Particle adhesion amount: 0.1mg / cm 2 ), and dried at room temperature for 24 hours to obtain each measurement sample. Next, the surface coated with the particles of the measurement sample was examined using a scanning probe microscope system (scanning probe microscope unit: AFM5100N, scanning probe station: AFM5000II) (manufactured by Hitachi High-Technologies Corporation) under measurement conditions (cantilever: SI-DF20P2, PM mode, scanning range: 20 μm × 20 μm, correction: quadratic curve), and the measured line roughness Ra of 500 nm was taken as the surface roughness Ra.

[0035] (4) Check for collapsibility 0.04 g of each particle dispersion (dispersion medium: ethanol, solid content concentration: 5%) was spread evenly on artificial leather (Laforet S2923) (5 cm x 4 cm) for 20 seconds (particle adhesion amount: 0.1 mg / cm 2), and dried at room temperature for 24 hours to obtain each measurement sample. Using a surface property measuring device Tribogear TYPE:14 (Shinto Scientific Co., Ltd.) (vertical load: 360 g, moving distance: 50 mm, moving speed: 600 mm / min), a jig (3 cm x 3 cm) with uncoated artificial leather (Laforet S2923) (3 cm x 10 cm) attached was used to rub the particle-coated surface of the measurement sample back and forth 10 times. Next, the rubbed surface of the measurement sample was observed at a magnification of 15,000 times using a field emission scanning electron microscope (FE-SEM) (model: 4800 (5.0 kV), Hitachi High-Technologies Co., Ltd.), and the major and minor diameters of 30 particles in the observed image were measured, and the average of the major and minor diameters was taken as the particle diameter of each particle. The volume-based particle diameter was calculated from the particle diameters of the 30 particles, and the average particle diameter D after rubbing was calculated. A ' Particles having a particle size ratio represented by the following formula (I) of less than 50% were defined as "easily disintegrating particles," and particles having a particle size ratio represented by the following formula (I) of 50% or more were defined as "non-disintegrating particles." Particle size ratio before and after scraping (%) = (average particle size after scraping D A ' / Average particle size before abrasion D A )×100 (I)

[0036] Examples 1 to 6 and Comparative Examples 1 to 4 An ethanol dispersion (dispersion medium: ethanol) of each adhesion inhibitor was prepared in the amount shown in Table 1, and the ethanol dispersion was used to perform evaluations according to the methods described below. The components shown in Table 1 are as follows. Average particle size D of inorganic particles (A) A , average primary particle diameter d A The surface roughness Ra and particle disintegrability are shown in Table 1.

[0037] [Inorganic particles (A)] Calcium silicate particles A1: Calcium silicate particles, trade name "Florite R", manufactured by Tomita Pharmaceutical Co., Ltd., oil absorption capacity 460 mL / 100 g Silica particles A2: Product name "Sunsphere H-31", manufactured by AGC Si-Tech Co., Ltd., oil absorption capacity 150 mL / 100 g, specific surface area 800 m2 / g, pore diameter 5nm, pore volume 1mL / g Silica particles A3: Product name "Sunsphere H-32", manufactured by AGC Si-Tech Co., Ltd., oil absorption capacity 300 mL / 100 g, specific surface area 700 m 2 / g, pore diameter 10nm, pore volume 2mL / g Silica particles A4: Product name "Sunsphere H-33", manufactured by AGC Si-Tech Co., Ltd., oil absorption capacity 400 mL / 100 g, specific surface area 700 m 2 / g, pore diameter 11nm, pore volume 2mL / g Silica particles A5: Product name "Sunsphere H-52", manufactured by AGC Si-Tech Co., Ltd., oil absorption capacity 300 mL / 100 g, specific surface area 700 m 2 / g, pore diameter 10nm, pore volume 2mL / g Spherical polymethacrylate particles AC1: Particles of lauryl methacrylate / ethylene glycol dimethacrylate / sodium methacrylate copolymer synthesized according to Example 1 of JP 2006-8980 A. Spherical silica particles AC2: Product name "SO-E4", Admatechs Co., Ltd., specific surface area 3 to 5 m 2 / g Fine particle silica AC3: Product name "AEROSIL R972", manufactured by Nippon Aerosil Co., Ltd., specific surface area 110±20m 2 / g Porous nylon particles AC4: Product name "POMP605", manufactured by Ube Industries, Ltd.

[0038] 〔evaluation〕 As Reference Example 1, skin to which no adhesion inhibitor had been applied and artificial leather as a substitute for skin were also evaluated in the same manner. <Evaluation of adhesion inhibition> The ethanol dispersion of the adhesion inhibitor was applied to white artificial leather (Laforet S2923) as a skin substitute at a deposition amount of inorganic particles (A) of 0.1 mg / cm 2 The coating was applied in an amount of 100 ml and dried at room temperature for 24 hours. In Comparative Example 3, the ethanol dispersion of the fine particle silica AC3 was prepared so that the adhesion amount of the fine particle silica AC3 was 0.01 mg / cm 2The surface of the artificial leather coated with the adhesion inhibitor was exposed to an airflow environment of the harmful air substances to be evaluated, and the color difference ΔE before and after exposure was measured using a spectrophotometer by the following method to evaluate adhesion inhibition. The results are shown in Table 1. [Measurement of color difference ΔE] Using a spectrophotometer (product name "NF 777", manufactured by Nippon Denshoku Industries Co., Ltd.), the L of the color of the artificial leather surface coated with the adhesion inhibitor before exposure to the atmospheric hazardous substances to be evaluated was measured. 1 * , a 1 * , b 1 * The values ​​were measured. Separately, a blower (product name "Silky Wind 9ZF002RH02", size: 129 × 106 × 83 mm, manufactured by Rhythm Watch Co., Ltd.) and a mesh sieve (Test sieves JIS Z 8801, frame dimensions: φ100 × 45H, mesh size: 106 μm, manufactured by Tokyo Screen Co., Ltd.) were fixed in a glove bag (product number: 3-118-01, manufactured by AS ONE Co., Ltd.). The height of the mesh sieve was set to 17 cm. The artificial leather (5 cm x 4 cm) coated with the adhesion inhibitor as a test sample was attached to a support so that the height of the bottom end of the artificial leather was 11 cm. The distance between the coated surface of the artificial leather on the support and the blower was 15 cm, and the blower was installed so that the coated surface of the artificial leather was perpendicular to the direction of airflow from the blower and the center height of the blower blades was the same as the center height of the artificial leather, as shown in Figure 1. The temperature inside the glove bag was set to 25°C and the relative humidity to 57%RH, and 0.05 g of the air hazardous substances for evaluation shown in Table 1 was classified from a mesh sieve using a clogging removal brush (product name "JNB-5", mesh size: for 106 μm or less, brush diameter 53 μm, manufactured by Tokyo Screen Co., Ltd.) while dropping it in front of the outlet of a blower with the air blowing scale set to 1 for 1 minute, exposing the surface of the artificial leather to which the adhesion inhibitor was applied to the air blowing environment of the air hazardous substances for evaluation. Next, the color difference of the exposed artificial leather surface was measured using the above-mentioned spectrophotometer. 2 * , a 2 * , b 2* The value was measured, and the color difference ΔE value was calculated according to the following formula (II). ΔE = [(L 1 * -L 2 * ) 2 +(a 1 * -a 2 * ) 2 +(b 1 * -b 2 * ) 2 ] 0.5 (II) The color difference ΔE of the artificial leather coated with the adhesion inhibitor of the test sample was taken as ΔEt, and the color difference ΔE of the artificial leather not coated with the adhesion inhibitor was taken as ΔEs, and the adhesion inhibitory effect was evaluated from the ratio of ΔEt to ΔEs (ΔEt / ΔEs) (N=3). If the ratio (ΔEt / ΔEs) is less than 1.0, the adhesion inhibitory effect of the air hazardous substances is achieved. The smaller the ratio (ΔEt / ΔEs), the better the adhesion inhibitory effect. The atmospheric hazardous substances for evaluation shown in Table 1 are as follows: Graphite powder: Product name "J-CPB", average particle size: 5.5 μm, manufactured by Nippon Graphite Industries Co., Ltd. Lycopodium: Product name "New Type Lycopodium", average particle size: 30-40μm, manufactured by Agri Co., Ltd.

[0039] <Evaluation of texture (smoothness)> Three expert panelists applied 0.02 mL of each adhesion inhibitor ethanol dispersion (adhesion inhibitor blend amount: 5% or 0.5%) to the inside of the forearm in a 3 cm diameter circle, and spread it evenly over 20 seconds under conditions of 25°C and 57% RH. Each panelist performed a sensory evaluation of the feel (smooth feel) after the ethanol dried four times according to the following criteria, and the average score of the three panelists was calculated. The results are shown in Table 1. 5: It feels very smooth. 4: Has a smooth feel. 3: Neither. 2: There is a creaking sensation. 1: It feels very squeaky.

[0040] [Table 1]

[0041] From Table 1, it can be seen that the air hazardous substance adhesion inhibitors of Examples 1 to 6 have a high adhesion inhibitory effect and also suppress deterioration in tactile sensation compared to the state where nothing is applied as in Reference Example 1. On the other hand, it is seen that Comparative Examples 1, 2 and 4 do not exhibit the adhesion suppression effect since they do not contain the inorganic particles (A). Also, in Comparative Example 3, although there is an adhesion suppressing effect, since the average particle diameter of the fine silica AC3 is 0.2 μm, it is understood that the deterioration of the feel is not suppressed. [Industrial Applicability]

[0042] The agent for inhibiting adhesion of atmospheric hazardous substances of the present invention has a high adhesion inhibiting effect and inhibits deterioration of the feel after application, and is therefore particularly useful as an agent for inhibiting adhesion of atmospheric hazardous substances when applied to solid surfaces. [Explanation of symbols]

[0043] 1: Sample to be evaluated 2:Support 3: Mesh sieve 4: Air hazardous substances for evaluation 5: Blower

Claims

1. An agent for suppressing the adhesion of atmospheric hazardous substances, comprising inorganic particles (A), The average particle diameter D of the inorganic particles (A) A an average particle diameter (A) of the inorganic particles (A) being 1 μm or more and 50 μm or less, a surface roughness (Ra) of the inorganic particles (A) being 10 nm or more and 50 nm or less, the inorganic particles (A) being silica particles, and the target for which adhesion is to be inhibited is the skin surface.

2. The agent for inhibiting adhesion of atmospheric hazardous substances according to claim 1, which does not contain a crosslinked (meth)acrylic acid ester-based resin powder having a compressive strength of 0.7 to 10 kgf / mm 2 .

3. A method for inhibiting adhesion of atmospheric hazardous substances, comprising applying the agent for inhibiting adhesion of atmospheric hazardous substances to a skin surface to inhibit adhesion of atmospheric hazardous substances to the skin surface.

4. The amount of the inhibitor for the adhesion of atmospheric hazardous substances is 0.01 mg / cm 2 3mg / cm or more 2 The method for suppressing adhesion of atmospheric hazardous substances according to claim 3, wherein the method is applied to the skin surface at a temperature of from 100 to 200° C.

Citation Information

Patent Citations

  • Self-cleaning surface, its manufacturing method and use thereof

    JP2002347159A

  • Solid powder cosmetic

    JP2011105626A

  • Cosmetic

    JP2012250917A

  • Liquid skin cosmetic composition

    JP2017109930A

  • Powder cosmetic composition

    WO2007141916A1